Prevalence of fast food consumption and associated factors among secondary school adolescents in Jigjiga Town Somali Region Eastern Ethiopia. - Ahmed Mohammed Ibrahim; Nasra Ali Hussein; Mohyadin Abdullahi Ahmed; Girma Tadesse Wadajo; Mohamed Omar Osman; Ramadan Budul Yusuf; Abdilahi Ibrahim Muse; Seid Muhumed Abdilaahi; Raymond Place; Jakob Zinsstag (PLoS ONE)
Background Fast food consumption is a growing public health concern and creates a burden of malnutrition and non-communicable diseases, especially among adolescents in low- and middle-income countries. Adolescents are particularly vulnerable due to increasing autonomy and exposure to unhealthy fast food environments. Adolescents are particularly vulnerable due to increasing autonomy and exposure to unhealthy food environments. Objective To assess the prevalence of fast food consumption and associated factors among secondary school adolescents in Jigjiga town, Somali region, Eastern Ethiopia. Methods An institution-based cross-sectional study was conducted. A total of 419 participants were selected using a systematic random sampling technique from six randomly selected secondary schools (2 public and 4 private schools). Data were collected using a structured questionnaire. Data entry was done using Epi-Data 3.1 and then was analyzed with SPSS version 23.0. Descriptive statistics were calculated, and logistic regression analyses were done to identify factors associated with fast food consumption. Variables with p-values <0.25 in bivariate analysis were included in the multivariable model. Adjusted odds ratios (AORs) with 95% CIs were reported, and finally statistical significance was declared at p-value < 0.05. Model fit was calculated using Hosmer and Lemeshow's test, and multicollinearity was checked using the Variance Inflation Factor (VIF). Results The prevalence of fast food consumption among adolescents was 49.2% (95% CI: 44.2, 54.1). Significant factors associated with consumption of fast food are being younger age (AOR = 2.02; 95% CI: 1.30, 3.16), being male (AOR = 1.94; 95% CI: 1.25, 3.01), living with individuals other than parents (AOR = 2.58; 95% CI: 1.51, 4.39), availability of fast food at home (AOR = 2.03 95% CI: 1.31, 3.14), having pocket money ≥ 500 ETB (AOR = 1.97; 95% CI: 1.12, 3.46), and being food insecure (AOR = 2.08; 95% CI: 1.32, 3.28). Conclusion Fast food consumption among adolescents in the study area is high, with higher consumption. Younger age, male gender, living with individuals other than parents, availability of fast food at home, higher pocket money, and household food insecurity were significantly associated with fast food consumption. Community-based and school interventions are needed to promote healthy food-consuming habits and reduce the health risks associated with frequent fast food intake in the study area.